Transcatheter mitral valve repair for functional mitral regurgitation using the Cardioband system: 1 year outcomes. (16th August 2018) - Messika-Zeitoun, David; Nickenig, Georg; Latib, Azeem; Kuck, Karl-Heinz; Baldus, Stephan; Schueler, Robert; La Canna, Giovanni; Agricola, Eustachio; Kreidel, Felix; Huntgeburth, Michael; Zuber, Michel; Verta, Patrick; et al.
Abstract: Aims: The Cardioband™ (Edwards Lifesciences) is a transcatheter implant designed to reduce mitral annulus size and mitral regurgitation (MR) severity. We report the 1-year outcomes of consecutive patients who underwent the Cardioband procedure between 2013 and 2016. Methods and results: Sixty patients with moderate or severe secondary MR (72 ± 7 years, 60% ischaemic origin) on guideline-recommended medical therapy were treated and analyzed at 11 European institutions. There were two in-hospital deaths (none device-related), one stroke, two coronary artery complications, and one tamponade. Anchor disengagement, observed in 10 patients (all but one in the first half of the population), resulted in device inefficacy in five patients and led to device modification half way through the study to mitigate this issue. Technical, device, and procedural successes, assessed based on Mitral Valve Academic Research Consortium (MVARC) criteria, were 97% (58/60), 72% (43/60), and 68% (41/60), respectively. At 1-year, overall survival, survival free of readmission for heart failure, and survival free of reintervention (performed in seven patients) were 87%, 66%, and 78%, respectively. In the overall population, MR grade at 12 months was moderate or less 61% and moderate or less in 95% of the 39 patients who underwent a transthoracic echocardiography at 1-year [but worsened by at least one grade in 11 patients (22%)]. Functional status (79% vs. 14% in New York Heart Association Class I/II), quality of life (−19 points on the Minnesota Living with Heart Failure Questionnaire score), and exercise capacity (+58 m by 6MWT) improved significantly (all P < 0.01). Conclusion: In this multicentre trial, the Cardioband mitral system demonstrated reasonable performance and safety. At 1 year, most patients had moderate or less MR and experienced significant functional improvements. A randomized controlled trial is underway to demonstrate the impact of Cardioband in patients on guideline-directed medical therapy. Abstract: